Pengalaman Perawat Intensive Care Unit Melibatkan Keluarga dalam Merawat Pasien End of Life Care: Reviu Literatur Perawat Intensive Care Unit Melibatkan Keluarga dalam Merawat Pasien End of Life Care: Literature Review - Rahman, Irfandi; Etnis, Baktianita Ratna; Kistan, Kistan (Health Information : Jurnal Penelitian, 2023)
The Intensive Care Unit (ICU) is a room with special equipment to provide treatment and critical nursing actions for those who are deteriorating. This literature review aim to describe the experience of nurses involving families in caring for end of life care patients in the ICU based on research that has been carried out. The method used in the literature review is to search for articles from qualitative studies, collected from electronic databases such as Google Scholar, Science Direct, and PubMed, using the MeSH Term keywords, namely: critical nurse, patient end of life, involve family, nursing experience . Selected articles between 2018-2023. This study from several articles is expected to reveal the phenomenon of the experiences of ICU nurses involving families in caring for end of life care patients. Theme: the need to involve the family, the challenges of involving the family in patient end of life care, nurses understanding the condition of patient end of life care in involving the family. The conclusion is that end of life care for patients in the ICU fulfills basic human needs holistically. Nurses can see patients as complete human beings by facilitating and assisting with necessary needs as well as involving the patient's family and being able to resolve patient problems in accordance with applicable procedures.